Local Vancomycin Concentrations after Intra-articular Injection into the Knee Joint: An Experimental Porcine Study - Bue, Mats; Thomassen, Maja B.; Larsen, Ole H.; Jørgensen, Andrea R.; Stilling, Maiken; Søballe, Kjeld; Hanberg, Pelle (The Journal of Knee Surgery, 2019)
Intra-articular injection of vancomycin may be an important antimicrobial prophylactic supplement to systemic administration in the prevention of prosthetic joint infections. In eight female pigs, 500 mg of diluted vancomycin was given by intra-articular injection into the knee joint. Microdialysis was used for dense sampling of vancomycin concentrations over 12 hours in the synovial fluid of the knee joint, and in the adjacent femoral and tibial cancellous bone and subcutaneous tissue. Venous blood samples were obtained as reference. The mean (standard deviation [SD]) peak drug concentration of vancomycin in the synovial fluid of the knee joint was 5,277 (5,668) μg/mL. Only one pig failed to reach a peak drug concentration above 1,000 μg/mL. The concentration remained high throughout the sampling interval with a mean (SD) concentration of 337 (259) μg/mL after 690 minutes. For all extraarticular compartments, the pharmacokinetic parameters (area under the concentration time-curve, peak drug concentration, and time to peak drug concentration) were comparable. The highest extraarticular mean (SD) peak drug concentration of 4.4 (2.3) μg/mL was found in subcutaneous tissue. An intra-articular injection of 500 mg diluted vancomycin was found to provide significant prophylactic mean concentrations for at least 12 hours in the synovial fluid of the knee joint. Correspondingly, the adjacent tissue and plasma concentrations were low but remained stable, signifying low risk of systemic toxic side effects and a slow release or uptake from the synovium to the systemic circulation.
Keywords: vancomycin; microdialysis; intra-articular injection; local antimicrobial administration; tissue concentrations